GAMBARAN KUALITAS PEWARNAAN TELUR CACING SOIL TRANSMITTED HELMINTH (STH) PADA FESES MENGGUNAKAN SARI KULIT BUAH NAGA MERAH SEBAGAI PENGGANTI EOSIN 2% - Imaniah, Nuril; Salman, Yuliana; Yahya, Yudi; Hidriya, Hajrah (Politeknik Unggulan Kalimantan, 2025)
Intestinal nematodes that often infect humans was soil transmitted helminth (STH) worms. This infection could have diagnosed by microscopic examination used an eosin 2% stained. Red dragon fruit was one typed of fruit that could used as a substitute for eosin 2%, especially for red dragon fruit skin, which was a wasted that is often founded in the surrounded environment. The purpose of this studied was to determine the effectiveness of red dragon fruit peeled as a substitute for eosin 2% for stained positive stools with STH worm eggs. This researched is an experimental studied with a completely randomized design (CRD) used a static group comparison pattern design with 24 experimental units. Red dragon fruit skin extract mixed with distilled watered at different concentrations, namely 1:1, 1:2, 1:3, 1:4, and 1:5, and compared with eosin 2% as a controlled. Inspection of STH is examined using native or direct methods. The results of the study based on the Kruskal–Wallis tested founded differences in the quality of staining at concentrations of 1:2, 1:3, 1:4, and 1:5, with eosin 2% as a controlled, while at a 1:1 concentration there was no significant difference with eosin 2% as a control. Based on these results, it can be concluded that red dragon fruit peeled extract is effective as an alternative dye for examined STH worm eggs at a concentration of 1:1, but the red dragon fruit peel extract dye did not produced a contrasting color liked eosin 2%.